Impact of corporate strategy on the digitalization of management control: evidence from Moroccan companies - El-Moumane, Rajae; Elhamma, Azzouz (European Scientific Journal, ESJ, 2024)
For several years, digitalization has emerged as a critical strategic issue for companies, influencing all of their functions, including Human Resources Management (HRM), logistics, finance, and others. It has been the subject of numerous research studies, particularly in developed countries. However, this type of research remains largely underexplored in developing countries. In this context, this paper, based on a survey conducted among forty-two companies in Morocco, aims to address two key questions. First, how can the degree of digitalization of management control in these companies be assessed? Second, does corporate strategy have a significant impact on this digitalization? The primary findings of the study suggest that the level of digitalization is "moderate." Furthermore, we demonstrate that corporate strategy significantly influences the digitalization of management control; specifically, prospector companies are more likely to adopt digital management control systems than defender companies. This research makes important contributions both theoretically and managerially. Theoretically, it provides new insights into the digitalization of management control. From a managerial perspective, it offers valuable guidance for decision-makers to better align the digitalization of management control systems with the broader strategic objectives of their organizations.